Institutional suicide as anomie: decedents speak out for work-related suicides through a Durkheimian exploration of suicide notes in a context without institutional responsibilization for suicide prevention - Ozbilgin, Mustafa F.; Erbil, Cihat; Demirbağ, Orkun; Gündoğdu, Nur; Şimşek Demirbağ, Kübra (Frontiers in Sociology, 2024)
Introduction Drawing on Durkheim’s historical theorization of suicide, we extend his concept of anomic suicide, which is suicide due to a lack of social regulation, to introduce the concept of institutional suicide. We define institutional suicide as suicide due to the absence or decline of institutional policies, practices, and discourses for prevention. In this study, we explore the mechanisms for institutional suicides based on suicide notes Turkey, in a context without institutional responsibilization for prevention. Turkey provides a significant context for studying institutional suicides as policies, practices, and discourses for suicide prevention have been declining for some decades. Methods Drawing on publically available suicide notes and narratives in Turkish media outlets, we analyze 17 suicide notes and responses from their institutions of work and friends, family, and colleagues. Findings and Discussion We identify two mechanisms that lead to institutional suicides: (1) dehumanization due to lack of recognition and (2) misrecognition through a devaluation of potential. We extend the theory of anomie to institutional settings and offer social policy suggestions to improve institutional responses based on co-design based on suicide notes to prevent institutional suicides and call for institutional responsibilization for preventing work-related suicides.